Are Auditors Biased? The Effect of Anchoring and Adjustment Heuristics on Auditors Judgment - Krida, Ashari; Pontjoharyo, Wiyono (Journal of Accounting Research, Organization and Economics, 2024)
Objective The objective of this paper is to illustrate one of the crucial factors that affect auditors in making their judgment which can lead to systematic error. This paper provides background on how heuristics and biases can affect the judgment of auditors to increase the awareness of the anchoring and adjustment heuristic on audit judgment.Methodology This research is a 2 x 2 experimental study which analyzes the employment of anchoring and adjusting bias of auditor in the process of making their audit judgment. This research employed three (3) experimental questions on 100 auditors in Surabaya, Indonesia, with experiences ranging from 0-8 years.Results The result indicates that is evident that anchoring and adjustment heuristic exist and affect auditors judgment. The findings also indicates that experience influence auditors judgment whereas gender does not have such effect on auditors judgment. However, experience and gender can moderate the effect of anchoring and adjustment heuristic on auditors judgment.Research limitations/implications The experimental questions used were simplified abstractions compared to the complex analytical reviews auditors typically encounter. Additionally, the sample size, consisting of 100 auditors, may limit the generalizability of the findings. The study exclusively focused on differences in auditor judgment influenced by anchoring and adjusting, without exploring potential contributions from other heuristic factors. Lastly, gender was categorized broadly as male and female, without further differentiation based on specific gender characteristics.Novelty/Originality Its originality lies in adding moderation variable of gender and experience. While prior research has explored the impact of behavior on audit judgment to enhance decision-making in auditing, none have investigated anchoring and adjustment heuristics while considering the moderating factors of gender and experience.